Nursing Intervention for Stroke Associated Pneumonia (SAP): Literature Review - Agustina Chriswinda Bura Mare (JURNAL NERS LENTERA, 2020)
Introduction: Stroke associated pneumonia (SAP) is a lower respiratory tract infection due to complications from stroke that occurs in the first 7 days after stroke onset in patients without ventilation. The aims of this study is to review the various literature on interventions that nurses can do to prevent and treat pneumonia in stroke patients. Methods: Search strategy by electronic databased, namely PUBMED, clinical key for nursing and AHA Journals. Articles published in 2010 - 2020 and in English. The inclusion criteria were research conducted on all stroke patients, both ischemic and hemorrhagic, the intervention given was a nursing action, and the outcome assessed was pneumonia. The exclusion criteria were pharmacological intervention and medical treatment. The keywords used are nursing intervention AND stroke associated pneumonia. Results: Seven articles were reviewed and found several interventions used to prevent and reduce the incidence of pneumonia in stroke patients. Nursing actions that can be done are dysphagia screening, early mobilization, swallowing therapy, and oral care. Conclusion: To be able to perform these actions properly and appropriately, nurses are required to attend training and continue to update their knowledge based on evidence based nursing practices. Keywords: nursing intervention, stroke, pneumonia